Consensus Conference 2021/2022: Physical and Rehabilitative Medicine – Diagnostic and Therapeutic Options (Part 2) - Best, Norman; Seidel, Egbert (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2022)
The 2021/2022 consensus conference covered the entire field of physical and rehabilitative medicine. In this second part, the results of the consensus conference with regard to rehabilitation medicine are presented (Part 1 published in Physikalische Medizin 2022; 54(02): 73–81). Aspects of this area of the specialty are presented comprehensively.
Keywords: physical therapy; rehabilitation medicine; consensus statement; specialist of PRM